NANOCOMPÓSITO DE ÓXIDO DE ZINCO INCORPORADO AO ÓXIDO DE GRAFENO MAGNÉTICO PARA ATENUAÇÃO DE RAIOS X - Silva, Adrine Silveira da (2024)
Conventional radiology, an excellent diagnostic imaging method, has been widely used in clinical practice. However, the search for new technologies that optimize image quality and minimize exposure to ionizing radiation drives research into advanced materials. In this context, nanocomposites based on magnetic graphene oxide (MGO) and zinc oxide (ZnO) emerge as promising candidates for the development of more efficient radiological shielding. The present study aimed to synthesize and characterize graphene oxide and ZnO nanocomposites, in order to evaluate their potential for X-ray attenuation. To this end, the following processes were carried out: synthesis and magnetization of graphene oxide and modification of the nanoparticles with zinc oxide. Subsequently, the nanocomposite was characterized by Fourier Transform Infrared Spectroscopy (FTIR), Energy Dispersive X-ray Spectroscopy (EDS), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). In addition, X-ray attenuation experiments were carried out using an X-ray apparatus. The results obtained through the exposure of the materials to the X-ray beam showed that the nanocomposites with magnetite proportions of 1:5 and 1:10 presented the best performance in terms of radiation attenuation. Moreover the duplication of the amount of material in these samples resulted in an increase in this attenuation. The results presented demonstrate the potential of the proposed nanocomposites for low-energy radiation attenuation.